2018
DOI: 10.1002/jbmr.3610
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocytes Promote Vascularization in Fracture Healing Through a FOXO1-Dependent Mechanism

Abstract: Chondrocytes play an essential role in fracture healing by producing cartilage, which forms an anlage for endochondral ossification that stabilizes the healing fracture callus. More recently it has been appreciated that chondrocytes have the capacity to produce factors that may affect the healing process. We examined the role of chondrocytes in angiogenesis during fracture healing and the role of the transcription factor forkhead box‐O 1 (FOXO1), which upregulates wound healing in soft tissue. Closed fractures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 58 publications
(114 reference statements)
1
26
0
Order By: Relevance
“…Both osteoblasts and hypertrophic chondrocytes express high levels of VEGF, which promotes both the aggregation and proliferation of endothelial MSCs into a vascular plexus, and growth of new vessels from already existing ones . It has recently been shown that the transcription factor FOXO1 mediates expression of VEGF by chondrocytes, which plays a significant role in angiogenesis during the transition from cartilage to bone in postnatal fracture healing . In the current study, we found that IFT80 in chondrocytes was necessary for blood vessel formation in fracture callus and was needed for expression of VEGF, PDGF, and angiopoietin 1.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…Both osteoblasts and hypertrophic chondrocytes express high levels of VEGF, which promotes both the aggregation and proliferation of endothelial MSCs into a vascular plexus, and growth of new vessels from already existing ones . It has recently been shown that the transcription factor FOXO1 mediates expression of VEGF by chondrocytes, which plays a significant role in angiogenesis during the transition from cartilage to bone in postnatal fracture healing . In the current study, we found that IFT80 in chondrocytes was necessary for blood vessel formation in fracture callus and was needed for expression of VEGF, PDGF, and angiopoietin 1.…”
Section: Discussionsupporting
confidence: 51%
“…(50) It has recently been shown that the transcription factor FOXO1 mediates expression of VEGF by chondrocytes, which plays a significant role in angiogenesis during the transition from cartilage to bone in postnatal fracture healing. (4) In the current study, we found that IFT80 in chondrocytes was necessary for blood vessel formation in fracture callus and was needed for expression of VEGF, PDGF, and angiopoietin 1. These data point to the important function of IFT80 in chondrocytes by contributing to the cellular events that occur in the formation of a hard fracture callus and provide mechanistic insight into the regulation of IFT80 in chondrocytes to promote angiogenesis.…”
Section: Journal Of Bone and Mineral Researchmentioning
confidence: 48%
See 2 more Smart Citations
“…Ginkgo biloba extract has shown a preservative effect on mesenteric arterioles of old rats through vascular elasticity and AKt/FOXO3a signalling pathway (Chen et al 2019). Angiogenesis in the fracture repair process is regulated by chondrocytes through FOXO 1-dependent upregulation of VEGFA mRNA, while silencing FOXO 1 reduces angiogenesis (Zhang et al 2019). Thus, a close relation between FOXO and ageing process is a key factor in maintaining vascular properties.…”
Section: Foxo Transcription Factorsmentioning
confidence: 99%